THE QUADRILATERAL ANALYSIS OF CEPHALOGRAM FOR THE TREATMENT OF GNATHIC FORMS OF MESIAL BITE - P.S. Flis; N.V. Rashenko; V.V. Filonenko; D.Y. Shpak; N.M. Doroshenko; A.V. Tsyzh (Ukrainian Medical Stomatological Academy, 2015)
Relevance of research. Enhancing the quality of diagnosis and planning of orthodontic treatment is an issue of great importance. Cephalometry is the most informative diagnostic method that allows assessing structural features of the skull base and facial skeleton of patients with bite anomalies. Prediction of dominated growth type of facial skeleton is important for selecting the optimal period of early orthodontic treatment, determining the treatment plan and forecasting results. The aim of the research. Increasing efficiency of mesial bite treatment by improving clinical and radiological diagnosis and the development of orthodontic appliances with rational design and indications for usage. Materials and methods. We examined 254 patients with mesial bite aged from 9 to 15 years. 74 patients with gnathic form of mesial bite without recommendations (evidence) to surgery on the jaws were accepted for treatment. 6 patients, who were recommended a comprehensive treatment, refused surgery and limited to orthodontic treatment only. For diagnosis, clinical and additional methods were used. We conducted lateral cephalometric analysis for 254 patients with mesial bite. Analysis was carried out using method of A. Schwarz and methods of Di Paolo, A. Bjork, R. Ricketts. Based on quadrilateral analysis by Di Paolo in determining dentoalveolar and gnathic form, we used the appropriate options for their differential diagnosis, using the formula (A'-B '+ M'-J') / 2; determined the required lengths A'- B '= M'-J' and compared the values with the actual length of the respective segments A'-B 'and M'-J'. According to Di Paolo, value M'-J 'and A'-B' reflects the height of the lower part of the facial skeleton. Its average value at neutral growth type is 65-67%. Reducing the value indicates the vertical growth type, increase - the horizontal one. Patients were divided into two groups: control and basic. The control group was treated with standard orthodontic appliances. The main group was treated with the proposed "Appliance for mesial bite treatment", consisting of a removable appliance for the treatment of mesial bite and facial mask. Results and discussion. The result achieved during the proposed method of treatment is not only lengthening the upper dental arch and curbing the mandible growth, but also the simultaneous expansion of the upper and lower dental arches. Mandible basis (B'J') barely increased in both groups due to usage of orthodontic appliance. Comparing treatment results in control and basic groups of patients with horizontal growth type, we observed that increasing the size of the maxillary base (A'M') was most active in the main group (difference - 4.1 mm). In patients with vertical and neutral growth type, we also observed that increase of the maxillary base size (A'M') was more active in the main group (differences 1.2 mm and 1.4 mm respectively). Conclusion. Using the proposed method of treatment with orthodontic appliance, one can increase efficiency and decrease active treatment period for patients with gnathic form of mesial bite and upper jaw micrognathia with any growth type of facial skeleton during active growth of dentognathic apparatus. The horizontal growth type has better results, as evidenced by the increase in the maxillary base size for 4.1 mm, comparing with vertical growth type - 1.2 mm, for neutral growth type - 1.4 mm.